Morbidity and mortality of domestic rabbits (Oryctolagus cuniculus) under primary veterinary care in England. (8th October 2019) - O'Neill, Dan G; Craven, Hermien C; Brodbelt, David C; Church, David B; Hedley, Joanna
Abstract : Background: The domestic rabbit is a common pet species, but limited research exists on the health of pet rabbits. This study aimed to characterise common disorders of pet rabbits and reasons for mortality as recorded by veterinary practices in England. Methods: This cross-sectional study covered anonymised clinical records of 6349 rabbits attending 107 primary veterinary care clinics. Results: The median age was 3.2 years (interquartile range (IQR) 1.6–5.1), and the median adult bodyweight was 2.1 kg (IQR 1.7–2.6). The most common breed types were domestic (n=2022, 31.9 per cent), lop (1675, 26.4 per cent) and Netherland dwarf (672, 10.6 per cent). For those rabbits that died during the study period, the median age at death was 4.3 years (IQR 2.1–7.0). The most common causes of death were recorded as myiasis (prevalence 10.9 per cent, 95 per cent confidence interval (CI): 7.4 to 15.2), anorexia (4.9 per cent, 95 per cent CI: 4.0 to 10.4), recumbency/collapse (4.9 per cent, 95 per cent CI: 4.0 to 10.4) and ileus (4.3 per cent, 95 per cent CI: 3.5 to 9.5). The most prevalent specific disorders recorded were overgrown claw/nails (16.0 per cent, 95 per cent CI: 14.5 to 17.5), overgrown molar(s) (7.6 per cent, 95 per cent CI: 6.6 to 8.7), perineal soiling (4.5 per cent, 95 per cent CI: 3.7 to 5.4), overgrown incisor(s) (4.3 per cent, 95 per cent CI: 3.5 to 5.2) and ileus (4.2 per cent, 95 per cent CI: 3.4 to 5.0). Conclusions: This study augments the limited evidence base on rabbit health and can assist veterinarians to better advise owners on optimal animal husbandry priorities.